Kajian Molekuler Ikan Sembilang (Neosilurus sp.) di Perairan Rawa Padi Kabupaten Merauke - Saleky, Dandi; Siruru, Meyani Anjelita; Sunarni, Sunarni; Pangaribuan, Rosa Delima (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Sembilang is one of the fish that is abundant in Merauke mainland waters. Genetic research needs to be done to prevent the decline of catfish population. DNA barcoding is a taxonomic method that uses short genetic markers in an organism's DNA to identify species. This research aims to identify the Sembilang fish species using the Cytochrome Oxidase I gene. This study is an exploratory survey research. Sample collection was carried out in the waters of Padi Swamp, Merauke Regency. The mitochondrial cytochrome oxidase I (COI) gene was amplified using the Polymerase Chain Reaction (PCR) method with FISH-BCL and FISH-BCH primers. The results of analysis using DNA barcoding revealed that the samples collected were the Sembilang species (Neosilurus ater) with a DNA sequence length of 660 bp. Phylogenetic reconstruction using the Neighbor-Joining method with the 2-Parameter Kimura Model shows sequence grouping based on similarity and genetic distance between species.